ANALISIS KESIAPAN GURU DI ERA MERDEKA BELAJAR DITINJAU DARI KOMPONEN TPACK DI SDN 20 BENGKULU - Yunisa, Sartika; Asiyah, Asiyah; Kurniawati, Esti Wahyu (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
The purpose of this study is to describe the readiness of teachers in the era of independent learning and the obstacles faced by teachers in preparing learning in terms of the TPACK (Technological Pedagogical Content Knowledge) component at SDN 20 Bengkulu City. This study is a qualitative descriptive study, data collection techniques using observation, interview and documentation methods. In this study, the subjects/informants were teachers and students in grades I, II, IV and V who had implemented the independent learning curriculum. The results of this study are that the readiness of teachers in grades I, II, IV and V in the era of independent learning in terms of the TPACK component at SDN 20 Bengkulu City has been running well, teachers understand the concepts, strategies and learning models according to the TPACK components. Teachers are also able to adapt the TPACK learning concept and model to the independent learning curriculum, but the availability of computers, projectors and wifi is still very minimal so that it becomes an obstacle for teachers in maximizing the process of integrating technology in the learning process.